STRATEGI GURU BIMBINGAN KONSELING DALAM PENGEMBANGAN KECERDASAN EMOSIONAL PESERTA DIDIK MELALUI PENINGKATAN LAYANAN BIMBINGAN KONSELING DI SMPN 4 PELEPAT ILIR - Rahmad Mustajab (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
Counseling guidance strategy is a series of activities that are arranged systematically that are tailored to the needs and problems of students. This activity is done to help clients overcome the problems that happen to cause rational thinking as the impact of good emotional intelligence. The purpose of this study is to describe describe the condition of students' emotional intelligence and counseling guidance strategy in developing the emotional intelligence of learners in SMP NEGERI 1 PELEPAT ILIR. This study focuses on the results of observations, documents and interviews of informants selected purposively. Deductive analysis is used to test the theory with facts obtained in the field.